Keramikken fra Farum Lillevang - Liebgott, Niels-Knud (Hikuin, 2001)
The pottery from Farum Lillevang By Niels-Knud Liebgott The pottery that was found when the kilns at Farum Lillevang were excavated in 1953 (see article on the Farum Lillevang Kilns) provoked a re-evaluation of the pre-existing view that all glazed and decorated pottery in medieval Denmark was imported from England or from the Netherlands. It was now demonstrated that the potters in Denmark could master the whole repertoire and make products of a standard equivalent to what was made in the large production locations abroad. Given the lack of other Scandinavian finds of medieval pottery production sites (no kiln has so far been found in the other Nordic countries), during the 1950s and 1960s many archaeologists believed, as one can observe in the archaeological publications from those decades, that all glazed pottery in those countries must have come from Farum Lillevang. This view has now been abandoned, not least in the light of the later finds of medieval pottery workshops in Denmark. The ceramic material collected during the investigations in Farum Lillevang in 1953 and 1970/71 amounted in all to some 6-7 tons. The way the sherd material has been handled since excavation has made systematic processing problematic. It can be established, however, that about 75% of all vessels produced in Farum Lillevang consisted of greyfired unglazed kitchenware – mainly globular and tripod pots. The glazed material consists chiefly of decorated or undecorated jugs with handles. A few matrices (stamps) used for the decoration of glazed pottery were found during the excavation (figs. 13-15). It seems that production in Farum Lillevang must have lasted for one decade at most. With a calculated success rate of 80% it can be estimated that the total of grey-fired vessels alone reaching the market must have been at least around 15,000. But only very few examples of finds outside Farum Lillevang can be associated with this production site with any degree of probability. There are a few vessels from Roskilde, that fall within this category (fig. 21).